Reconstruction of input signal of sensor with frequency output - Pawlowski, Eligiusz (2015 20th International Conference on Methods and Models in Automation and Robotics (MMAR), 2015)
The sensor with frequency output converts the measured quantity to the pulse signal, the instantaneous frequency of which is proportional to the instantaneous values of the input signal. Measurement of the pulse signal frequency is always a measurement of a mean value and direct measuring of its instantaneous value is not possible. The paper contains the analysis of the principles of operation of the frequency output sensor and an appropriate generalized flow chart. A processing algorithm allowing to reconstruct the input signal on the basis of digitally measured time intervals between the subsequent impulses of the output signal is presented. The suggested approach is presented using the example of an incremental rotary encoder and a Voltage-to-Frequency Converter.